2009
DOI: 10.1007/s10640-009-9287-3
|View full text |Cite
|
Sign up to set email alerts
|

Testing the Effectiveness of Certainty Scales, Cheap Talk, and Dissonance-Minimization in Reducing Hypothetical Bias in Contingent Valuation Studies

Abstract: Stated preference methods such as contingent valuation and choice modeling are subject to various biases that may lead to differences between actual and hypothetical willingness to pay. Cheap talk, follow-up certainty scales, and dissonance minimization are three techniques for reducing this hypothetical bias. Cheap talk and certainty scales have received considerable attention in the literature, but dissonance minimization has not previously been experimentally tested. Using a four-way split sample design inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
90
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 131 publications
(96 citation statements)
references
References 45 publications
5
90
0
1
Order By: Relevance
“…List (2001) and Lusk (2003) found that Cummings and Taylor's (1999) cheap talk script lowered bids for inexperienced (unknowledgeable) consumers while Brown et al (2003) and Murphy et al (2005) concluded it was indeed successful but only for high payment amounts. Blumenschein et al (2007) on the other hand, found that cheap talk has no significant impact while the results of Morrison and Brown (2009) suggest that it can overcalibrate responses and underestimate the actual WTP. Earlier attempts also failed to match the hypothetical with the actual WTP.…”
Section: Cheap Talkmentioning
confidence: 99%
See 1 more Smart Citation
“…List (2001) and Lusk (2003) found that Cummings and Taylor's (1999) cheap talk script lowered bids for inexperienced (unknowledgeable) consumers while Brown et al (2003) and Murphy et al (2005) concluded it was indeed successful but only for high payment amounts. Blumenschein et al (2007) on the other hand, found that cheap talk has no significant impact while the results of Morrison and Brown (2009) suggest that it can overcalibrate responses and underestimate the actual WTP. Earlier attempts also failed to match the hypothetical with the actual WTP.…”
Section: Cheap Talkmentioning
confidence: 99%
“…Would you be willing to pay XX cents so that you can avoid exchanging it with a pack of conventional strawberries without any certification? [show picture 2]" Following the literature on certainty scales (Champ et al, 1997;Morrison and Brown, 2009), every CVM discrete choice question was followed by a question asking respondents to state how certain they were about their response on a 10-point scale anchored with the labels "Not certain at all" and "Very certain" .…”
Section: Experimental Design and Questionnaire Developmentmentioning
confidence: 99%
“…3 The validity of web-based surveys has been questioned but, so far, a majority of recent studies found no evidence of any systematic bias (see for example Lindhjem and 3 To the best of our knowledge, web-based surveys have not been found to reduce the hypothetical bias commonly present in contingent valuation studies. Although considerable attention has been devoted to various techniques (cheap talk, follow-up certainty scales, dissonance minimization, see Morrison and Brown, 2009) for reducing the hypothetical bias, these techniques are still under debate and were not implemented in the 2008 OECD Survey on Household Environmental Behaviour.…”
Section: Previous Estimates Of Willingness To Pay For Better Drinkingmentioning
confidence: 99%
“…The initial study of Blamey et al (1999) showed DM questions elicit steeper demand functions, but they do not contrast their result with a real setting. Morrison and Brown (2009) compares the performance of DM with both: calibration and cheap talk. Among the three elicitation devices, only cheap talk fails to discipline revelation since it provides an over-correction of hypothetical bias (average yes votes are lower than in the real treatment).…”
Section: The Economics Of Preference Revelationmentioning
confidence: 99%